PENGARUH PENDAPATAN ASLI DAERAH, SISA LEBIH PEMBIAYAAN ANGGARAN, PINJAMAN DAERAH TERHADAP REALISASI BELANJA MODAL SUMATERA SELATAN - Pika, Pika; Saiful, Saiful; Aprila, Nila (UNIB Press, 2018)
This study aims to determine the effect of Original Revenue, Remaining More Budget Financing, Regional Loans on Capital Expenditures Realization in Districts / Cities Se-Province of South Sumatra. This research data is taken during the last three periods between 2014-2016 with the number of samples of 17 regencies and municipalities in South Sumatra Province as many as 48 observations. This research uses the report of realization of APBD of Government / City of South Sumatera Province in 2014-2016. In this research, it is obtained by using purposive sampling method with criterion 1) which preparing Budget Realization Report in the last 3 (three) years, 2) Regency / Municipality which publishes Budget Realization Report which published in last 3 (three) years. This study tested the hypothesis by using multiple linear regression.The result of this research of Original Regional Revenue proved to have a positive effect on the realization of capital expenditure, the remaining budget financing proved to have a positive effect on the realization of capital expenditure, and regional loan was not proven to have a positive effect on capital expenditure